IF THE TRANSITION ECOLOGICAL TAKEN PLACE ... A PROSPECTIVE SOCIOLOGICAL TO ENLARGE THE DISCUSSION ON RESPONSIBILITY COMPANIES - Christoph B. STAMM (ORGANISATION RESPONSABLE, 2015)
The notion of ecological transition is increasingly present in the discourse of various actors. While its definition often remains vague, its apparition might be more due to the search for a new term to replace the worn out concept of sustainable development, than to real political change. In this paper, the ecological transition is conceptualized as the societal shift from a model which prioritizes economic growth to a model which focuses on environmental sustainability. An evaluation of the current contribution of governments, the green movement and corporations in reducing the environmental impact leads to the observation that they lack the capacity and willingness to initiate the aforementioned transition, necessary to prevent widespread ecological collapse. Therefore, we adopt a foresight approach and develop a scenario in which a sustained oil price increase results in the unintended end of the growth model. These events would empower the actors of change and open possibilities to transform the social institutions towards a post-growth society. With this scenario in mind, the article discusses the corporation’s role and responsibility in the transition.